Impact of financial incentives for infection prevention and management on antibiotic use: A Korea National Health Insurance cohort study - Yu Shin Park; Soo Young Kim; Hyunkyu Kim; Suk-Yong Jang; Eun-Cheol Park (Elsevier, 2024)
Background: The Korean government implemented financial incentives to enhance infection prevention and management within general hospital settings. This study aimed to evaluate the impact of infection control compensation on antibiotic usage using a controlled interrupted time series analysis. Methods: The main unit of analysis was 270,901 inpatient episodes extracted from the Korean National Health Insurance Service Cohort Database from 2013 to 2019. The 96-month period was examined before and after the intervention, which was set to September 1, 2017, by applying a 1-year lag time after the incentive was introduced. Segmented regression was used to estimate the effects of interventions in a controlled interrupted time series. Hospitals that received nationwide financial incentives for infection prevention and management were included in the analysis. The study's primary outcome was the use of antibiotics based on the WHO Access, Watch, and Reserve (AWaRe) classification of antibiotics, and the secondary outcome was the number of days of antibiotic use as days of therapy (DOTs) per patient day (PD). Results: The probability of overall antibiotic use decreased between incentivized and unincentivized hospitals (odds ratio [OR], 0.922; 95% confidence interval [CI], 0.859-1.000). The difference in level change in the use of third-generation cephalosporins (OR,0.894; 95% CI, 0.817-0.977) and carbapenem (OR,0.790; 95% CI, 0.630-0.992) was significantly reduced between incentivized and unincentivized hospitals. The difference in slope change on DOTs/PD of glycopeptides was − 0.005 DOT/PDs, and that of carbapenem was − 0.003 between incentivized and unincentivized hospitals. Conclusion: We observed that incentives for infection prevention and management have had a positive impact on some aspects of antibiotic usage. A partial decrease was observed in antibiotic use, accompanied by a modest reduction in DOTs/PD, particularly for antibiotics aimed at addressing multidrug-resistant pathogens. Further investigation is necessary to establish evidence for extending these incentives.